Penerapan Model Pembelajaran Realistic Mathematics Education (RME) untuk Meningkatkan Hasil Belajar Siswa Kelas 1 SD Negeri 2 Sugihan - Sukartiyem Sukartiyem (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Mathematics is knowledge that plays an important role in the development of science and technology. Mathematics is one of the important subjects for students to master at school because it has many uses in everyday life. The aim of this research is to apply the Realistic Mathematics Education (RME) Learning Model to Improve the Learning Outcomes of Class 1 Students at SD Negeri 2 Sugihan for the odd school year 2021/2022. This type of research is Classroom Action Research (PTK). The data analysis technique in this research is comparative descriptive analysis, where the results from cycles I and II are compared with the learning outcomes. Then the student's learning outcomes are said to be successful if they reach Minimum Completeness (KKM), which is a minimum of 70. Classical completion is said to be successful if at least 85% of the total number of class students have reached the KKM, which is a minimum of 70. The results of this research are an increase from cycle I with students completing as many as 11 students with a percentage of 61.11% became 16 students with a percentage of 88.89% in cycle II.